Provenance-Finding of Dust Storms Using AVHRR Sensor Images of NOAA Satellite (Case Study: Southwest of Iran) - Mohammad Hossein Rezaei Moghaddam; Mojtaba Mahdian Boruojeni (جغرافیا و پایداری محیط, 2016)
1- Introduction Dust storm is considered as one of the most important challenges in the west of Asia which has been intensified in recent decades due to various reasons like drought. These storms move a huge amount of soil particles causing severe economic, social and health damages. Iran, located in West Asia, is frequently exposed to dust storms due to being on arid and semi-arid belt. Studies have shown that for many years, storms have occurring in the west and southwest of Iran and neighboring countries. Moreover, in some cases, these storms have moved dust and sand of prone areas with themselves. However, the storms and the concentration of transported material have not been as sever as the recent years.The occurrence of these storms in the past few years have violated the common life of people in the.However, the prevention of this phenomenon is inevitable because of its scope; its adverse effects can be reduced by studying temporal – spatial accumulation of dust. Moreover, we can both do management practices and take effective steps to eliminate or at least reduce the severity of this phenomenon and prevent its development by tracking produced dust and identification of its origin at local and regional scale. The present study aims at identifying the origin and dust removal centers located in the southwest of Iran's borders. 2- Materials and Methods In this study, investigating the dust of the southwest of Iran, AVHRR sensor of NOAA satellite have been used to identify the origins of dust storms. In this regards, using coded data of synoptic weather stations that represent different dusty days per hour, 24 AVHRR imagery were prepared. Pre-processing stages including geometric and radiometric correction were done on the images to prepare them. After preparing the images, in the processing stage, the particles were identified by applying the dust detection algorithms including brightness temperature differences in the thermal infrared bands (band 4&5 AVHRR sensor) and false color combination (R: 1 G: 2 B4). 3- Results and Discussion Detecting the images, a total of 62 origin points were extracted in the southwest of the country which were transferred to the GIS environment. Using the functions of density distribution, three regions with the highest density in the accumulation of dust are introduced as three important areas in the southwest of the country producing dust. The particles are more affected by the northwest winds and the diffusion of pollution to the southeast. The first area is located in the southwest of Ilam province and bordering of this province with Iraq, which has the highest number of points allocated in terms of density. The dust formed in this area, often does not enter the country affecting the neighboring country. The second area is located in the southern border of Ilam province, the northern border of Khuzestan Province and the crossing with Iraq and around it whose dust enters the northwest of Khuzestan and sometimes goes to the center. The third area is located in the west of Khuzestan, bordering of Iraq and the lowlands next to Hooralazim pond. Although the density of origin points and the repetition of dust pollution is much are a lot, is different from the other two previous area in terms of dust volume. Dust pollution of this area drawn to the south of Khuzestan. 4- Conclusion In general, using 24 AVHRR images and the use of detection techniques, a total 62 points were identified as the source of dust production. Citing the total accumulation of these points, three regions were found as the dust producer in the southwest of Iran. The findings of this study are in accordance with the previous studies and other satellites such as MODIS images that have been conducted in the southwest of the country, in which the same regions are recognized as the source of sand production. Studying the identified areas producing dust in terms of environmental conditions shows that existence of sensitive geological and soil conditions to erosion and low vegetation as the soil protector heavily accelerate their potential in dust production.